RESTORATION OF LARGE MODULAR TEETH OF BALL MILL GEARS BY ELECTRO-SLAG SURFACE - Smailova, Baglan; Buzauova, Toty; Bartenev, Igor; Davletova, Kunsulu (Journal of Applied Engineering Science, 2024)
This article is devoted to researching the possibility of restoring straight-toothed large-module gears by electro-slag surfacing of individual defective teeth. During the work, an installation was designed and manufactured to restore gears that do not require further machining. A comparative analysis of the proposed technology with the traditional surfacing technique was carried out, paying attention to variables such as the composition of the surfacing material used, process parameters, stabilization of the electro-slag process, and ensuring the geometric dimensions and profile of the tooth. The study results demonstrate that the proposed technology provides higher hardness and wear resistance of remanufactured parts compared to traditional methods.
Keywords: large-module gears, tooth wear, electro-slag surfacing, ball drum mills, crystallizer